2005
DOI: 10.1063/1.1929075
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembled monolayer-enhanced hydrogen sensing with ultrathin palladium films

Abstract: Resistive-type palladium structures for hydrogen sensing remains as a research focus for their simplicity in device construction. We demonstrate that a siloxane self-assembled monolayer placed between a substrate and an evaporated ultrathin Pd film promotes the formation of small Pd nanoclusters and reduces the stiction between the palladium and the substrate. The resulting Pd nanocluster film can detect 2 % H 2 with a rapid response time of ϳ70 ms and is sensitive to 25 ppm hydrogen, detectable by a 2% increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
191
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 219 publications
(198 citation statements)
references
References 23 publications
7
191
0
Order By: Relevance
“…It has been shown that the use of ultrathin discontinuous Pd films [11] offers a simple solution to realize a hydrogen sensor that could fulfill many of those requirements. Discontinuous films are commonly deposited by physical vapor deposition (PVD) techniques such as electron-beam evaporation.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the use of ultrathin discontinuous Pd films [11] offers a simple solution to realize a hydrogen sensor that could fulfill many of those requirements. Discontinuous films are commonly deposited by physical vapor deposition (PVD) techniques such as electron-beam evaporation.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 In particular ultrathin palladium ͑Pd͒ films have been recently attracting increased attention as an application in resistive hydrogen ͑H 2 ͒ gas sensing for fuel cell safety systems. 5,6 Here, the volume expansion that occurs in Pd nanoclusters at hydrogenation 7,8 is exploited to reversibly narrow or even close the film-inherent nanogaps. New percolation pathways are thus formed and lead to a decrease in electrical resistance ͓see Fig.…”
mentioning
confidence: 99%
“…13͒ or selfassembled monolayers. 6 However, the characteristics of the interjacent transition regime itself and related changes in electrical response to hydrogen have not been studied yet. Our investigations show that this transition is of a gradual nature and is characterized by a semicontinuous film regime 2,14 that results in characteristic physical properties and distinct responses at H 2 exposure.…”
mentioning
confidence: 99%
“…14,15 Bimorph micro-and nano-mechanical structures are a convenient solution from the point of view of their compatibility with standard top-down techniques developed in the semiconductor industry over the years 16 and their ultra-low power consumption. However, deflection-based (or amplitude-based) mechanical sensors, regardless of the transduction technique, suffer from the fact that any external source of noise directly offsets the electrical signal that is the output from the device and thereby reduces the resolution of the sensor.…”
Section: Introductionmentioning
confidence: 99%